Análisis de la viabilidad del aprovechamiento del acero proveniente de los residuos cortopunzantes en la ciudad de Bogotá (2017)
The feasibility of recovering the steel contained in sharps waste in Bogotá was analysed, specifically those generated in Health Services or similar establishments supervised by the District Department of Health of Bogotá. This was done by analyzing production patterns, regulations and current processing and treatment technologies available in Colombia. A cost comparison was made including current management and a proposed scheme for recovering the steel contained in sharps waste in Bogotá. With the potential of extending the lifespan of the landfill along with possible economical benefits, it was envisaged that it is feasible to recover the steel contained in sharps waste in Bogotá.